Molecular Mechanism of Parnassiapalustris in the Treatment of Cervical Cancer Based on Network Pharmacology - Yan Ru Liu, Si Yuan Tang, Jing Liu, Li Xia Luo, Jing Da Yu (Forest Chemicals Review, 2022)
Background: A series of evidence suggests that thechemicalconstituentssuch as dichloromethane extracts and ethylacetateextractsfromParnassiapalustris caninhibite the proliferation of cervical cancer cells (Hela).But the mechanism of chemicalconstituentsfrom Parnassiapalustris on Cervical Cancer are not Clear, the mechanismswould be reveal based on network pharmacology and molecular docking. Methods: Main chemical components parnassiapalustris Linn were collected based onliteratrues, and parnassiapalustris’stargets were obtained by Swiss Target Prediction database,SEA search server database and BANTMAN database. Main targets of cervical cancer were obtained from genecards. Common targets betweenparnassiapalustris and cervical cancer were obtained by venndiagram. Cytoscape software and string database were used to construct a network of "parnassiapalustris-components–cervical cancer targets" and protein interaction network(PPI). The Top3 key targets were to dock to extracts from parnassiapalustris,and compounds with the better binding degree were screened for the mechanism of action analysis. Results: 102 targets were obtained related to parnassiapalustris treatment of cervical cancer,the top three protein targets were SRC,EGRF and ESR1. Molecular docking results showed that main active components had good binding activity with their corresponding target proteins,especially,kaempferol-3-rutinoside，hyperoside,quercetin,Kaempferol and chlorogenic acid and celahin Bhad the best absolute values of the docking scores with all three protein targets. Conclusions: All results show thatParnassiapalustris has characteristics of multi-component, multi-target and multi-pathway on cervical cance, The main active components for the prevention and treatment of cervical cancer in extract of parnassiapalustris were kaempferol-3-rutinoside,hyperoside, quercetin,kaempferol,chlorogenic acidand celahin B. All conclusions could providethe basis for cervical cancer clinical application.